#metoo: The Good, the Bad, and the Backlash - Tranchese, Alessia (From Fritzl to #metoo: Twelve Years of Rape Coverage in the British Press, 2023)
I start this discussion in this chapter with an outline of the key points within the #metoo debate, looking at what, according to various scholars, has and has not been achieved since the hashtag went viral in 2017. This overview constitutes the context for the subsequent analysis and critical evaluation, which will look at how the press conceptualised #metoo, and how it shaped some of the wider discussions about the hashtag. In Chapter 11, it will focus on whether (and how) the widespread use of #metoo after 2017 affected the representation of violence against women in the British press compared to the previous years.
Keywords: Irina

Now About All These Women in the Swedish Film Industry - Wallenberg, Louise; Papadopoulou, Frantzeska; Koskinen, Maaret; Soila, Tytti (Bloomsbury Academic, 2023)
In the aftermath of the MeToo movement, during an ongoing pandemic, and in the midst of repeated demands for a 50/50 split between men and women in above-the-line positions, this book analyzes and interrogates the politics of gender focusing on the Swedish film industry, often considered to be the most "gender equal" film industry worldwide. While this gender equality (with a considerable proportion of women behind the camera) is much due to policies carried out of the state funded Swedish Film Institute, women filmmakers in Sweden still struggle with the same problems as do women in other national film industries. These problems entail having smaller production and distribution budgets than men and working in an environment involving recurring scandals of gender discrimination and sexual harassment. This open access book looks behind the statistics and explores the often complex cultural, legal, and political conditions under which women have entered a male-dominated industry and discusses women’s strategies and efforts to promote change while providing evidence on how women’s presence has challenged the industry by provoking critical reactions and introducing new ways to portray women on screen. Using a wide range of different sources (e.g. archival material, laws, contracts, films, biographical materials, and interviews), the book tells the history of the rise of gender equality efforts undertaken by the Swedish Film Institute and investigates women’s possibilities to manage the rights to their work. It offers compelling portraits of pioneering women who have worked in or in relation to the industry and looks at the experiences of women currently working in the film industry. The ebook editions of this book are available open access under a CC BY-NC-ND 4.0 licence on bloomsburycollections.com. Open access was funded by Örebro universitet.
Keywords: Irina; Metoo; Sweden; Swedish Film Institute; TV & radio::APF Films; change; cinema::APFA Film theory & criticism; cinema::APFN Film: styles & genres; conditions; discrimination; equality; film industry; filmmakers; male-dominated; pioneering; politics of gender; rights; scandal; sexual harassment

Working with “monstrous men”: ambivalent sexism in the Bombay film industry - Sanchez Lozoya, Zeltzyn Rubi (Feminist Media Studies, 2022)
In India, the 2012 Delhi gang rape case catalyzed protests for women’s rights, particularly in regard to their safety. These demands were rekindled with vigor anew with the eruption of the #MeToo movement. In the Indian film industry, the most visible change appeared in the gradual increase of films with womenleads. But behind the scenes, there has been comparatively less change in female representation. Currently, approximately less than 10% of film directors in India are women. Considering the impor tance of having stories about women being made by women, in this article I examine the factors that hinder women’s entrance and tenure in the Mumbai film industry. I argue that a composite of concerns, including but not limited to reputability and personal security, thwarts women’s progress in the industry. I base my con clusions on interviews with women and men working in the film industry, conducted in Mumbai in 2017. I use the framework of the Ambivalent Sexism Index developed by psychologists Glick and Fiske in 1996, and revised in 2013, (1996, 2001, 2013) to examine my interviewees’ encounters with hostile and benevolent sexism. This article complicates our understanding of the reasons that limit the work of women beyond explanations of overt discrimination.
Keywords: Irina

Sex and safety on set: intimacy coordinators in television drama and film in the VOD and post-Weinstein era - Sørensen, Inge Ejbye (Feminist Media Studies, 2022)
This article examines the work of intimacy coordinators on television drama and film sets and the rise of this new role in the screen industry from a policy and production studies perspective. Since HBO made the employment of an intimacy coordinator mandatory on all productions with scenes of sex, nudity, and physical intimacy in 2018, intimacy coordination has become an industry standard and expectation. Through interviews and analysis of production practices, this article explores how intimacy coordinators change and challenge established production practices on and off set and interrogates the reasons behind the emergence of this role in the screen industry. It situates intimacy coordination in the context of recent industry policies and initiatives that promote equality and diversity, and counter harassment and abuse in the post-Weinstein era. It analyses this role on relation to changing production and distribution models and regimes in the era of VOD portals. The article argues that intimacy coordination is not only a catalyst for reforming practices on set, but a way for the screen industry to negotiate contemporary and historic concerns about sexual harassment and abuse, comply with recent policy and funding requirements, and a mechanism for mitigating economic and reputational risk to productions.
Keywords: #MeToo; Intimacy Coordination; Irina; Prévention; VOD; equality; screen industries

Time for a change: women, work, and gender equality in TV production - Milner, Susan; Gregory, Abigail (Media, Culture & Society, 2022)
This article uses Acker’s concept of inequality regimes to analyze qualitative research findings on work-life balance and gender equality for women in British television production. Female survey respondents, focus group participants, and interviewees spoke of their subjective experience of gendered work practices which disadvantage women as women. These findings build on existing research showing gender disadvantage in the industry, leading to loss of human capital and a narrowing of the range of creative experience. They also show that growing numbers of women are seeking alternative modes of production, at a time of increased awareness of inequality. Such alternatives suggest that change is possible, although it is strongly constrained by organizational logics and subject to continued resistance, in line with Acker’s framework of analysis. Visibility of inequalities is the key to supporting change.
Keywords: Myriam; TV; TV production; Television

Women actors, insecure work, and everyday sexism in the Canadian screen industry - Liinamaa, Saara; Rogers, Malia (Feminist Media Studies, 2022)
Acting, especially in the screen arts industry, is a job where women are subjected to pronounced and widely accepted socio-cultural aesthetic ideals within an industry that has become renowned for its tolerance for and justifications of sexism and sexualized violence. However, there is a limited amount of scholarship that examines actors and acting from a work and employment perspective. Drawing on the literature on work insecurity and gender inequities in cultural work, this article examines the screen industry from the perspective of women actors in a semi-peripheral location in Canada. This is a cohort that has managed to remain in the industry, despite high levels of attrition. Drawing on in-depth semi-structured interviews, our participants identify a range of strategies they employ (toughness, silence, humour, refusal, creative resistance) to respond to workplace sexism and gender-based constraints as they try to balance their creative agency with career sustainability. Participants emphasized that finding multiple outlets for realizing creative agency is crucial to counteracting everyday sexism and remaining in the industry.
Keywords: Bibliographie; Irina; Nettoyer; Screen industry; everyday sexism; gender and cultural work; women actors and acting

Understanding Sexual Harassment in the #MeToo Era - Julios, Christina (Sexual Harassment in the UK Parliament: Lessons from the #MeToo Era, 2022)
This chapter provides a contextual account of the rise of #MeToo as an global gender-equality campaign supporting those affected by sexual transgressions. Originally articulated by African-American civil rights activist Tarana Burke in 2006, the slogan ‘me too’ was meant as a rallying cry to support young minority ethic survivors of sexual abuse. Years later, social media would turn Burke’s motto into a byword for the global #MeToo movement. The chapter chronicles the events surrounding #MeToo’s inception, including Hollywood producer Harvey Weinstein’s sexual exploitation scandal in 2017, and The New York Times and The New Yorker exposés of his serial offending within the film industry. It also examines the narratives of countless survivors and #MeToo campaigners, including high-profile cases such as those of Rose McGowan, Alyssa Milano, Mimi Haleyi, Jessica Mann and Zelda Perkins. The chapter then critically considers the growth and international significance of #MeToo as well as its inherent shortcomings.
Keywords: #MeToo; Farrow; Harvey Weinstein; Irina; Kantor and Twohey; Rose McGowan

The impact of #MeToo in the South African film and television industry, within a historical framework - Majiba, Ntsika (Université de l'Afrique du Sud, 2022)
The study is a history project and is concerned with tracking the impact of #MeToo in the South African Film and Television industry in South Africa. Its main premise were the findings made public by a South African organization, Sisters Working in Film and Television (SWIFT) in 2017, that found that sexual harassment in the television and film industry was not just a norm but a crisis. The core focus of the study was on the development and impact of the #MeToo movement, which entailed investigating the manner in which women reacted to the hashtag (#MeToo), the reaction of their male counterparts, as well as the reaction and actions taken by the various bodies, institutions and organisations in the Film and Television industry, which included; broadcasters and production houses alike. This study begins by giving a concise background of the movement by firstly, historicising various female-led movements and comparing and contrasting them with the rise of digital movements or digital activism. The historicisation involves a brief comparison of past and present women-led activism, as well as a brief review of other hashtags like #AmINext and #Enough, on which #MeToo has had an influence. It goes on to investigate the development of #MeToo movement and to discuss the responses of the industry and individuals to the movement. The study embarked on a data collection quest by interviewing eleven female television and film practitioners in South Africa. Their ages ranged from 20 to 55. The findings of the research revealed that female practitioners were still being harassed post #MeToo, although subtly. The lack of unity amongst women in the sector was cited as one of the reasons behind the ongoing harassment. Gender parity and equity was also still lacking in the South African television and film industry. This study emerged in the midst of activism and scholarship seeking to unravel the norms of South African sexual harassment and rape culture against women. Thus, the study focused on the changes and transformations brought about by the hashtag within the industry. With South Africa’s historical background and the current circumstances around Gender Based Violence (GBV), this study was concerned with tracking whether or not digital activism had in some way been able to aid change and transformation. In particular, this study looked at the impact of the MeToo phenomenon on the women in the industry, the extent to which it empowered them, what they began to say and how they began to act. The study also explored South Africa’s ‘rape culture’ as South Africa has been proclaimed the ‘worlds rape capital’. It reflected on the colonial rule as the perpetuation of patriarchy and male entitlement over female bodies. Patriarchy in the industry was also confirmed by the findings and through data analysis, as one of the key factors in the emergence of #MeToo in South Africa, and in the utilisation of the hashtag by women in the sector to speak up against sexual harassment.
Keywords: Bibliographie; Irina; Nettoyer

Creative Industries in Canada - Thompson, Cheryl; Campbell, Miranda (Canadian Scholars, 2022)
Keywords: Cultural industries.; Irina

The Routledge Companion to Romantic Love - Brooks, Ann (Routledge, 2021)
Keywords: Irina

Narrating women workers’ perceptions of sexism and change in the Australian screen postproduction sector before and after #MeToo - Dooley, Kath; Erhart, Julia (Feminist Media Studies, 2021)
This article interrogates the localized experiences of present-day workers who identify as women in Australian postproduction sectors, including editing, visual effects (VFX), and animation, exploring sex ism and perceptions of change in the age of #MeToo. Considering the significant numbers of women working in these sectors, and the scant research into their experiences undertaken in an Australian context, the authors conducted semi-structured interviews with ten women in various roles and in various geographical locations in Australia. This qualitative approach to data collection aims to explore inequalities that may not be captured in industry surveys, providing fine-grain details of the ways that individuals in postproduction experience sexism. The resulting data suggests that while there is continuity between the gendered experiences of these workers and that of women in industry sectors that have already been documen ted, there are, however, new observations about changes in work place behavior in the sector, brought about by growing public awareness of industry discrimination and harassment and of shifts in Australian industry policy. The authors isolated recurring themes within women’s gendered experiences in relation to how they per ceived the impact of the gender-equity initiatives on the attitudes of their co-workers, their workplace opportunities, and their experi ences as workers.
Keywords: Irina

“The balance of power is me: 0, Harvey Weinstein: 10”: A Critical Discourse Analysis of the press representation of Hollywood’s biggest sexual harassment scandal - Nikolova, Evelin (Women's Studies International Forum, 2021)
On 5 October 2017, The New York Times published an article in which Harvey Weinstein was accused of sexual harassment by five women. The scandal grew to enormous proportions as more allegations against him followed. This led to the #MeToo and TIME'S UP movements, initiatives to fight sexual harassment in the workplace. Given that media discourse can have an impact on the knowledge, beliefs, attitudes, and behaviours of the public regarding these phenomena (van Dijk 1989), this study adopts a Critical Discourse Studies (CDS) perspective and explores how power and gender inequality are sustained, (re)shaped and/or challenged by focusing on the reporting of the Harvey Weinstein case which - to the author's best knowledge - has not been analysed before in the field of linguistics. It draws from the systemic functional linguistics and the discourse-historical approach and it examines the way the perpetrator, the accusers and the phenomenon of sexual harassment were discursively constructed in five key articles published in the New York Times. The findings differ in a major way from existing research on sexual violence against women in that 1) the perpetrator, Weinstein, was depicted with clear ascription of agency, 2) women victims' voices and feelings were foregrounded, 3) the link between sexual harassment and the social context in which it occurs was discussed.
Keywords: Critical discourse studies; Discourse-Historical Approach; Discursive strategies; Media representation; Myriam; Sexual harassment; Transitivity analysis; Weinstein

Me Too: The Effects of Sexual Harassment and Assault in the Entertainment Industry - Gaal, Cassandra (Backstage Pass, 2020)
Keywords: Entertainment Industry; Myriam

“These things happen”: Hashtag activism and sexual harassment in the South African film and television industries - Paleker, Gairoonisa (Agenda, 2020)
In August 2017, the South African advocacy group Sisters Working in Film and Television (SWIFT) launched the #ThatsNotOk campaign, which has to date produced six episodes of short films (one episode in two parts, making it seven in total) elucidating the different forms sexual harassment takes, and the different scenarios in which it occurs, in the South African film and television industries. This profile engages with SWIFT and the Public Service Announcement (PSA) films as discursive sites and texts respectively, and provides textual analyses of the PSAs in the context of digital feminism and feminist activism against sexual harassment in the film and television industries. The profile motivates that as expressions of digital feminism, the PSAs critique the pervasiveness and normalisation of sexual harassment, while failing to engage with or critique the neoliberal logic and structure of the film and television industries.
Keywords: #ThatsNotOk; Irina; South African film and television; digital feminism; hashtag activism

Gender Equality in British Film-making: Research, Targets, Change - Cobb, Shelley; Williams, Linda Ruth (Women in the International Film Industry: Policy, Practice and Power, 2020)
In October 2017, the British Film Institute declared that it would commit to specific targets for gender equality and diversity in key production roles on films with support from the Film Fund. This decision by the BFI to set targets, arguably, did not come just from their own diversity and inclusion goals. Activist film-makers had previously called for targets for the Film Fund, especially for women directors. This chapter will give an accounting of the current state of gender (in)equality in the UK industry by: outlining new research that has clarified the stagnant inequality in the UK film industry; articulating the key role of a network of activist groups (that include researchers, professional and campaigning bodies, exhibitors and film-makers) to bring attention to the problem; putting pressure on the film industry and public bodies; and summarising institutional responses to that pressure since 2016, with a critical analysis of the potential and limits of the BFI’s relatively recently implemented diversity and equality targets.
Keywords: Bibliographie; Irina; Nettoyer

#TimesUp on Individual Litigation Reform: Combatting Sexual Harassment through Employee-Driven Action and Private Regulation - Dugan, Natalie (Columbia Journal of Law and Social Problems, 2020)
Keywords: Bibliographie; Irina; Nettoyer

Sexual Harassment in the Post-Weinstein World - Grossman, Joanna L. (UC Irvine Law Review, 2020)
Keywords: Myriam; film industry

Experiencing Male Dominance in Swedish Film Production - Jansson, Maria; Wallenberg, Louise (Women in the International Film Industry: Policy, Practice and Power, 2020)
Sweden has been hailed for its recent success in increasing the number of female directors, scriptwriters and producers. Published reports, panel discussions and a vast number of press conferences on the pressing matter of gender equality within the industry together with a 5050 quota have all put the Swedish film industry—and its CEO Anna Serner—on the map. However, the last couple of years has disclosed several scandals regarding sexism and discrimination in the Swedish film industry—just as in other national film industries. This paper sets out to discuss how female film workers (e.g., directors, actors and producers) understand and negotiate their experiences of male dominance within their work context. Based on a series of interviews with women working in Swedish film from the early 1960s until today, we analyze similarities and differences in experiences as well as how these experiences are explained by the interviewees. Their stories are analyzed by using feminist institutional theory to understand how policy, funding schemes and other institutional aspects are intertwined with their experiences. The paper sets out to analyze three themes: (1) comments and suggestions during production and post-production regarding female protagonists; (2) experience of gender trouble in the process of fundraising; and (3) strategies used by the interviewed filmmakers to produce a more women-friendly environment during productions.
Keywords: Irina

Women in the International Film Industry: Policy, Practice and Power - Liddy, Susan (Springer International Publishing, 2020)
Keywords: Irina

The impact of intervention measures on sexual harassment in the film and television industry - Eng, Ben; McKinney, Ralph; Shao, Lawrence (Journal of International Management Studies, 2019)
Since 2017, increased sexual harassment incidents have been reported in Hollywood; yet, little guidance has been offered on how organizations, which are informally governed by their network members, can effectively reduce sexual harassment. Building upon the theory of network governance, this paper suggests social mechanisms, which are used to coordinate and safeguard exchanges between Hollywood organizations, are more effective at reducing incidents of workplace sexual harassment than traditional strategies. These social mechanisms direct change to the macroculture through collective sanctions that damage the perpetrators reputation and restrict access to network opportunities. In essence, perpetrators become toxic assets that Hollywood avoids and this avoidance is similar to economic sanctions that can deter sexual harassment.
Keywords: Bibliographie; Irina; Nettoyer

The Experiences of Women Professionals in the Film Industry in Turkey: A Gender-Based Study - Gürkan, Hasan (Acta Universitatis Sapientiae, Film and Media Studies, 2019)
The article is based on 20 in-depth interviews with women professionals conducted for a more comprehensive study focusing on gender roles within the film and television industry in Turkey. This study examines the career possibilities for women, the experience of being a woman working in television and cinema, and the working environment, including work-life balance issues, experiences of discrimination and experiences of sexism. The hypothesis of this study is that film industry is male-dominated, and women have to struggle to be able to prove themselves in this industry in the 21st century in Turkey, where the position of women is made even more difficult by the gender role codes and the structure of Turkish society.
Keywords: Irina

The Experiences of Women Professionals in the Film Industry in Turkey: A Gender-Based Study - G&#252, Hasan; rkan (Acta Universitatis Sapientiae, Film and Media Studies, 2019)
The article is based on 20 in-depth interviews with women professionals conducted for a more comprehensive study focusing on gender roles within the film and television industry in Turkey. This study examines the career possibilities for women, the experience of being a woman working in television and cinema, and the working environment, including work-life balance issues, experiences of discrimination and experiences of sexism. The hypothesis of this study is that film industry is male-dominated, and women have to struggle to be able to prove themselves in this industry in the 21st century in Turkey, where the position of women is made even more difficult by the gender role codes and the structure of Turkish society.
Keywords: Myriam; Turkey; film industry; gender; gender role; women

#MeToo, Time's up, and Theories of Justice - Wexler, Lesley; Robbennolt, Jennifer K.; Murphy, Colleen (I) (University of Illinois Law Review, 2019)
Keywords: Irina

Hard facts, soft measures: Gender, quality and inequality debates in Danish film and television in the 2010s - Redvall, Eva Novrup; Sørensen, Inge Ejbye (Journal of Scandinavian Cinema, 2018)
Abstract This article investigates discussions about gender, quality and equality in Danish film and television in the 2010s. Contrary to Sweden, where gender diversity has been part of public debate and formal screen policy since the 2000s, there was little discussion of gender in the Danish screen industry until the Danish Film Institute (DFI) began focusing on diversity as a priority area before the Film Strategy for 2015–18. The article analyses how both DFI and industry players have continuously argued against gender quotas, instead opting for soft measures such as ‘gender declarations’ and initiatives to raise awareness. One of these initiatives was a manifesto, ManusFestet, that used humour to raise questions about gender representation on-screen. The article discusses how a balance between hard facts and soft measures seems to be experienced as a constructive way forward, as long as this combination does in fact facilitate the intended change.
Keywords: Irina

Post Weinstein: gendered power and harassment in the media industries - Cobb, Shelley; Horeck, Tanya (Feminist Media Studies, 2018)
Keywords: #MeToo; Bibliographie; Irina; Nettoyer

What sexual harassment in Zentropa tells us about cultural policy post-Weinstein - Sorensen, Inge (Feminist Media Studies, 2018)
Keywords: Irina

The Right of One's Own Image in the Recent Cases of Sexual Harassment in Film Industry: Applying the European Theory of Concentric Circles to Celebrities (In Particular, Women) - Corredoira, Loreto (Journal of Information Policy, 2018)
Keywords: Irina

Reconceptualizing Sexual Harassment, Again Collection: #MeToo and the Future of Sexual Harassment Law - Shultz, Vicki (Yale Law Journal Forum, 2018)
Keywords: Irina

Sexual Harassment in the Creative Industries: Tolerance, Culture and the Need for Change: Sexual harassment in the creative industries - Hennekam, Sophie; Bennett, Dawn (Gender, Work & Organization, 2017)
The economic, social and cultural contributions of the creative industries are essential elements of many societies and their governments’ policies. However, there is growing evidence that precarity, competition and lack of regulation within these industries is exacerbating inequalities with respect to gender, race and class. With a focus on gender and sexual harassment among female workers, this study involved 32 in-depth interviews with women working in the Netherlands’ creative industries. Data were analyzed using content analysis. Findings suggest that sexual harassment is prevalent, and many women considered it to be part of their occupational culture and career advancement. Four factors inﬂuenced this phenomenon: competition for work; industry culture; gendered power relations; and the importance of informal networks. Implications include the need for a climate of non-tolerance, sector-speciﬁc research and guidelines, sensitivity training and further work with unions and professional associations to provide worker protection strategies traditionally undertaken by organizations. The article concludes that effective sexual harassment prevention requires action at the individual, educational, sectoral and governmental levels, beginning with public conversations to convey the message that sexual harassment is never acceptable.
Keywords: Bibliographie; Irina; Nettoyer

Women Harassment at Workplace: A Study of Pakistani Television Channels - Zia, Anjum; Batool, Sumera; Yasin, Zaeem (2016)
The present study explores the contemporary status of women harassment in Pakistani media industry taking alongside theoretical consideration of liberal feminism theory. An empirical method was adopted and in-depth interviews were conducted with media employees of both genders at television channels of the country. The study examined six core dimensions of harassment including working environment of the organization, male dominance, women harassment at workplaces, stereotype thinking patterns about women, offensive remarks on appearance of female colleagues and reporting of harassment issues to explore the current situation of women harassment in television channels of high repute. Findings of the study revealed that regardless of their ample role in thriving Pakistani media, women journalists are facing harassment at their workplaces but majority of them lesser likely to report harassment issues. Existence of stereotype thinking patterns about women and offensive remarks about appearance of women point towards severity of situation about women harassment at Pakistani media industry. Interestingly, despite male domination in media industry, general environment of media organizations is reported as satisfactory at large, whereas research concludes with highlighting areas for people working within and outside media organizations to eradicate harassment at workplaces. Keywords: Women harassment, male dominance, stereotype thinking patterns, Pakistani media, reporting of harassment.
Keywords: Myriam; Television

Gender then, gender now: surveying women's participation in Australian film and television industries - French, Lisa (Continuum : Journal of Media and Cultural Studies, 2014)
In the Australian audiovisual industries, women are a minority of the personnel in a large number of key creative roles and have considerably lower representation than in the Australian workforce generally. Despite the decline in their participation across several fields, the under-representation of women is not being addressed by these industries. Using findings from current research that includes a major survey of Victorian activity, this article engages with the urgent need for new approaches to thinking about the contribution and innovation of women: culturally, creatively and economically. Benchmarked against the last major study in 1992 (Cox and Laura), pivotal issues examined include barriers to progression, representation by job type and workplace/organizational cultures, along with a consideration of the current successes (relative to other areas) of women in television. Business, cultural and social arguments are made for the importance of gender equity, and an understanding of the contribution and value of women to these industries.
Keywords: Bibliographie; Irina; Nettoyer